Amidation of amino ethylene-1,2-dicarboxylic acid diesters: a theoretical consideration - Lebed, О.S.; Chertikhina, Yu.А.; Mutaliyeva, B.Zh.; Kudasova, D.Е.; Prosyanik, А.V. (KSU publ., 2019)
The amidation features of the Z- and E-isomers of amynoethylene-1,2-dicarboxylic acid diesters MeO2CCN=C(NRR1)CO2Me, where R = Н; R1 = H, Me, t-Bu; R = R1 = Me, have been considered based on the data of quantum chemical calculations in the PBE/def2-TZVPP approximation in the framework of Natural Bond Orbital (NBO). Amino-fumaric acid derivatives were chosen as objects for analysis since activated enamines containing conjugated enamine and carbonyl groups in their structure are one of the promising classes of regulators. It was shown by the calculations that for enamines I-IV, regardless of their configuration, conformers with α-s-trans, β-s-cis-arrangement of C=C and C=O bonds are most beneficial. These findings are consistent with experimental data on the relative configurational stability of the Z- and E-isomers of N-alkylaminoethylene-1,2-dicarboxylic acid diesters. The direction of the amidation reactions depends critically on the structure of the reactant and the reaction conditions. It was established that the amidation of amino acid-1,2-dicarboxylic acid diesters obeys to orbital control of the reaction. The observed regiospecificity of non-catalytic amidation on the α-ester group was explained by the joint influence of a decrease in the electrophilicity (increase in the energy of the loosening π-orbital) of the β-carbonyl group due to effective conjugation with the π-system of the C=C–NHR and an increase in the electrophilicity of the α-carbonyl group with an increase in its conjugation with the rest part of the molecule. The inertness of N,N-dimethylaminomaleate to reactions with amines is caused by the increased energy of π* С=О-orbitals of ester groups. Bis-amidation of amino-ethylene-1,2-dicarboxylic acid diesters is possible only in the presence of catalysts.
Keywords: amidation; quantum chemical calculations; activated enamines; regiospecificity; conformers; cisoid arrangement of bonds; transoidal arrangement of bonds; isomers; orbital control